S-band SLM distributed Bragg reflector fiber laser - Ahmad, Harith; Azhari, N.S.; Zulkifli, M.Z.; Muhammad, F.D.; Harun, Sulaiman Wadi (IOP Publishing, 2014)
Generation of single longitudinal mode operation based on distributed Bragg reflector (DBR) cavity configuration, using a depressed-cladding erbium-doped fiber as the gain medium collectively with fiber Bragg grating (FBG) and Faraday rotator mirror (FRM) performing as the end mirrors, is proposed and demonstrated in this work for operation in the S-band region. The FBG has a central wavelength of 1506 nm, which functions to restrict the lasing frequency. A small line-width value measured at 20 kHz has been achieved in this system. A graph of average pump power against output power establishes the measured slope efficiency at about 0.01%.